Kesadaran Masyarakat Terhadap Pentingnya Keamanan Konstruksi Bangunan Rumah Tinggal Terhadap Bencana Badai Angin, Banjir dan Gempa - Pratiwi Mushar; Victor Sampebulu; Nasruddin -; Hartawan -; Imriyanti -; Teguh Iswara S; Taufik Ishak; Dahniar -; Yusaumi Ramadhanti F.T (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2021)
The Gowa Regency is an area with the rapid development of housing and settlements. Some of the causes are the availability of land that is still a lot, the less space to build in urban areas so that development leads to suburban areas. This provides opportunities for local communities to improve their economy, developers to get opportunities in their business and the government to realize low-cost housing programs. Residentials that are developed independently or held by developers require fast building completion without considering the feasibility of building construction against site conditions, and natural disasters (floods, winds and earthquakes). It is reported that buildings' safety and security cannot be separated from topography and soil conditions, hence the planning must be able to adjust geological and geographical conditions wisely and wisely. The purpose of the activity is socialization to assist the community in responding to the security conditions of houses that are built independently/buy with ready for habitation. Partners are residents of Balang Balang village. The method used is a discussion with the head of the local RT and an initial survey of the condition of the partner buildings is continued to the socialization stage. The output is the concept of the “Disaster Response Building” model as a driver of “Community Awareness regarding the Importance of Security for Residential Building Construction against Disasters. The benefit of the activity is the response of the community to the importance of the safety of residential construction.